Diencephalic syndrome in child with NF-1 and hypothalamic tumour - Pilotto, Chiara; Thomas, Adam; Howarth, Simon P.S.; Didcock, Liz; Thomas, Shery; Walker, David A. (2018)
We describe a 20 month old boy with neuro-fibromatosis type 1 (NF-1) who presented with diencephalic syndrome due to a large hypothalamic tumour and developed massive necrosis after chemotherapy associated with severe encephalopathy.